Fast and sensitive taxonomic classification for metagenomics with Kaiju - Peter Menzel (Nature Portfolio, 2016)
Here, Anders Krogh and colleagues describe Kaiju, a metagenome taxonomic classification program that uses maximum (in-)exact matches on the protein-level to account for evolutionary divergence. The authors show that Kaiju performs faster and is more sensitive compared with existing algorithms and can be used on a standard computer.